Control Strategies of Papaya Mealybug, Paracoccus marginatus Williams and Willink in the Laboratory Condition - Biswas, M.J.H.; Khan, M.A.M.; Ahmed, K.S. (International Journal of Applied Sciences and Biotechnology, 2015)
The laboratory experiment was conducted at the laboratory of the Department of Entomology, Bangladesh Agricultural University to determine the effectiveness of polythene band, predatory ladybird beetles (available species found in Bangladesh viz. Coccinella transversalis (F.), Micraspis discolor (F.), Menochilus sexmaculatus (F.), Cyclonida sanguinea, Adalia bipunctata, Coccinella novemnotata and Illeis koebelei), four chemical insecticides and three botanical oils in controlling papaya mealybug, Paracoccus marginatus Williams and Granara de Willink. The chemical insecticides were Sevin 85 SP, Dimethoate 40 EC, Fipronil 50 EC, Deltamethrin 2.5 EC, and the botanical oils were Neem oil, Mahogany oil and Karanja oil. In the laboratory experiment, polythene banding failed to prevent the plant from the infestation of papaya mealybug. Seven commonly available species of ladybird beetles in Bangladesh did not provide any control to papaya mealybug. Among the chemical insecticides, Sevin 85 SP and Dimethoate 40 EC showed significant mortality of papaya mealybug. Deltamethrin 2.5 EC and Neem oil (2%) provided moderate control of the pest. The remaining insecticides and botanical oils were less effective to control papaya mealybug. Int J Appl Sci Biotechnol, Vol 3(4): 687-691